2016
DOI: 10.3126/jcmsn.v11i4.14319
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Side Effects of Chemotherapy among Cancer Patients in B.P. Koirala Memorial Cancer Hospital Bharatpur, Nepal

Abstract: jdjBackground & Objectives: These side effects of chemotherapy affect the patients’ daily life and quality of life adversely. It affects the different body system resulting in physical and non physical (psychosocial) side effects. Cancer patients demand information to understand chemotherapy-related adverse effects and actions to be taken. The aim of the study is to find out the perception of side effects of chemotherapy among cancer patients.Materials and methods: A descriptive cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 3 , 9 On the other hand, side effects of chemotherapeutic agents are other concerns. 21 The mi-RNAs like miR-155 play a crucial role in cell fate as small potent molecules with different targets. Rokah et al demonstrated that Philadelphia chromosome in CML cells can downregulate the expression of miR-155.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 9 On the other hand, side effects of chemotherapeutic agents are other concerns. 21 The mi-RNAs like miR-155 play a crucial role in cell fate as small potent molecules with different targets. Rokah et al demonstrated that Philadelphia chromosome in CML cells can downregulate the expression of miR-155.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs have side effects because in addition to destroying the actively dividing cancer cells, they damage the actively growing normal cells (5) . These side effects of chemotherapy affect the patients' daily life and affect the different body system resulting in physical, psychological and cognitive side effects (6) . Chemotherapy treatment for cancer has been associated with fatigue, pain, depressive symptoms which is main trigger for suicidal behavior, and disturbed sleep, poor sleep quality is a risk factor for exacerbation of chronic pain (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to affecting the physical condition, recent research such as that conducted by Gurung and Pandey in Nepal or Sasaki, et al in Japan stated that chemotherapy also affects the patient's non-physical condition such as work, household duties or the patient's partner, this is even more complained by patients than physical problems (Gurung & Pandey, 2016;Sasaki et al, 2017). This indicates a possible shift from the impact of chemotherapy that is experienced based on the patient's own perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise with cancer patients who undergo chemotherapy. The perception or assessment of each patient regarding the side effects experienced is also different (Gurung & Pandey, 2016).…”
Section: Introductionmentioning
confidence: 99%